The identifiable victim effect: a meta-analytic review. (2nd July 2016) - Lee, Seyoung; Feeley, Thomas Hugh
Abstract: The identifiable victim effect (IVE) refers to individuals' tendency to offer greater help to specific, identifiable victims than to anonymous, statistical victims. A random-effects meta-analysis was conducted to determine the overall weighted effect of IVE. Overall, 41 studies were included. Results indicated an overall significant yet modest IVE ( r = .05). In addition, findings showed that IVE appears reliable mainly when there is a single identified or a single unidentified victim, and/or when study characteristics include elements of the following: a photographed child suffering from poverty, bearing little responsibility for the need, and/or associated with monetary requests. The implications of the findings and directions for future research are discussed.